2015
DOI: 10.1038/nri.2015.4
|View full text |Cite
|
Sign up to set email alerts
|

Specialized pro-resolving mediators: endogenous regulators of infection and inflammation

Abstract: Specialized pro-resolving mediators (SPMs) are enzymatically derived from essential fatty acids and have important roles in orchestrating the resolution of tissue inflammation -that is, catabasis. Host responses to tissue infection elicit acute inflammation in an attempt to control invading pathogens. SPMs are lipid mediators that are part of a larger family of pro-resolving molecules, which includes proteins and gases, that together restrain inflammation and resolve the infection. These immunoresolvents are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
458
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 548 publications
(500 citation statements)
references
References 203 publications
5
458
0
5
Order By: Relevance
“…3B). The 15-epi LXA 4 is the 15(R) epimer of LXA 4 , yet these epimers have distinct biosynthetic pathways (11). As a control, we also used the coculture system to assess transcellular generation of LXA 4 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3B). The 15-epi LXA 4 is the 15(R) epimer of LXA 4 , yet these epimers have distinct biosynthetic pathways (11). As a control, we also used the coculture system to assess transcellular generation of LXA 4 .…”
Section: Resultsmentioning
confidence: 99%
“…As increasing FEV 1 /FVC ratio remains a key therapeutic objective of clinical therapy, one strategy may be direct replacement of the absent proresolving lipid mediator. Multiple studies have demonstrated that exogenous administration of specialized proresolving mediators improves morbidity and mortality outcomes following infection (11). In particular, the administration of a LXA 4 analog in mice challenged intratracheally with P. aeruginosa led to reduced neutrophil infiltration, weight loss, and bacterial burden, resulting in overall lessening of disease severity (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its well-known role as a pharmaceutical target for anti-inflammatory drugs in inflammatory diseases, COX-2 also exerts versatile biological activities to resolve inflammation (7)(8)(9). At the onset of inflammation, COX-2 has a potent proinflammatory effect, predominantly through the generation of PGE 2 , whereas in the resolution phase, COX-2 is responsible for producing proresolving PGs, such as PGD 2 , 15-deoxy-D 12,14 -PGJ 2 , and PGF 2a (10)(11)(12)(13).…”
mentioning
confidence: 99%
“…By using the fat‐1 mouse model, in which ω‐3 PUFAs are endogenously formed from ω‐6 PUFAs, ω‐3 PUFAs were found to boost remyelination 117. Some of the anti‐inflammatory effects of ω‐3 PUFAs may be explained by the fact that they act as precursors of anti‐inflammatory resolvins and protectins 118, 119. Unlike ω‐3 PUFAs, ω‐6 PUFAs have been suggested to be proinflammatory and may stimulate T H 17 cell activation,120 likely by acting as precursors of inflammatory lipid mediators, such as eicosanoids 120.…”
Section: Involvement Of Fatty Acids In Cns Autoimmunity: Saturated Vementioning
confidence: 99%